Transformative Learning and Assessment in Non Formal Education - Gail Goulet (Adult Education Research Conference, 2010)
This paper and presentation explore the intersection of transformative learning and assessment to highlight the various parts assessment plays in fostering transformative learning. Instructors, graduate students, trainers, and researchers in adult education who research or work with adults where there is a purposeful, or unintended, possibility of transformative learning experiences will further their understanding of the types and possible uses of assessment of transformative learning.